Rhabdomyosarcoma of a 7 year-old girl from Bangladesh: A case report with review of literature - S.M. Anwar Sadat; Mushfiq Hassan Shaikh; Md Badruddoza (Oral and Maxillofacial Surgery Cases, 2020)
Rhabdomyosarcoma is a malignant skeletal muscle neoplasm which frequently involves head and neck region. It is the second most common soft tissue sarcoma encountered in children. RMS is an aggressive neoplasm with extensive local invasions and early hemorrhagic and lymphatic dissemination. Here, we report a case of oral RMS in a 7-year-old girl from Bangladesh. Histologically, the tumor consisted of a classic embrayonal rabdosarcomatous area was observed in the biopsy specimen. Furthermore, we discuss about the clinical, radiological, immunohistochemical findings, and management of the aforementioned RMS case.